CAPACIDADE COMBINATÓRIA DE LINHAGENS E SELEÇÃO DE HÍBRIDOS DE MILHO FORRAGEIRO - Paiva, Elida Auxiliadora Peralta (2017)
The aim of current study was to evaluate the combining ability of maize inbred lines and hybrids as to agronomic and forage suitability. The 11 inbred lines originated from two base populations and 30 hybrids obtained by a partial diallel cross 6x5 were analyzed in randomized block design with three replications and were carried in three environments, Rio Bonito do Iguaçu in the season 2014/2015, Guarapuava in the season 2014/2015 and Guarapuava in the season 2015/2016. There were used the index Z of combining ability estimates and phenotypic means to select experimental hybrids for forage usage. The following characteristics were evaluated: male flowering (FM), plant height (AP), ear height (AE), grain yield (PG), staygreen (SG), forage’s dry matter yield (PMS), neutral detergent fiber (FDN), acid detergent fiber (FDA), in situ digestibility (DIG) and forage’s digestible dry matter yield (PMSD). There were significant differences between the genotypes for the features, except for the FDA and DIG. There was no significant difference for the interaction genotype x environment only for the DIG. There were also significant difference detected for general combining ability (CGC) and for specific combining ability (CEC) in all characteristics. The hybrids 29-35 x 30-122 and 29-35 x 30-160 were outstanding for agronomic characteristics and grain yield in the three environments, showing high averages, high CEC and suitable CGC by at least one parent. For the forage features the hybrid 29-109 x 30-08 presented the hightest values in the environments AMB1 and AMB3, presenting favorable estimates of CEC for the forage characteristics set.